Amorphous calcium carbonate as a novel potential treatment for osteoarthritis in dogs: a pilot clinical study - Sarig-Rapaport, Hadas; Krupnik, Sigal; Rowan, Tim G. (Frontiers in Veterinary Science, 2024)
Amorphous calcium carbonate (ACC) is a potential new treatment for canine osteoarthritis (OA) with novel mechanisms based on local pH modulation and targeting bone remodeling, inflammation, and pain. The aim of this pilot, exploratory clinical study was to obtain initial data on the potential efficacy and safety of ACC in OA dogs and to determine if further investigation was appropriate using similar assessment methods. In this prospective, randomized, double-blind, controlled pilot study, 41 client-owned dogs were allocated in a 2:1 ratio to ACC: Placebo given orally, for 56 days. Efficacy assessments included improvements in pain and mobility using owner questionnaires (Canine Brief Pain Inventory (CBPI), Client Specific Outcome Measure (CSOM)) and Veterinary Orthopedic Scores (VOS). Safety in the study population was monitored by veterinary examinations, clinical pathology, and adverse events. Results: Fifty-three dogs were screened, of which 41 enrolled and served for the safety assessment. 36 dogs were found evaluable for initial efficacy assessment. Three dogs given Placebo (21.4%) and one given ACC (4.5%) were removed before day 56 due to owner-perceived pain and were considered treatment failures. There were no serious adverse events nor clinically significant treatment-related effects in the study. Overall, ACC was found safe in the small study population. On day 56, proportionally more ACC than Placebo dogs were treatment successes based on CBPI (45.5% vs. 21.4%) and CSOM (63.6% vs 30.8%, respectively); however, these differences were not statistically significant (P= 0.15 and 0.06, respectively). On day 56, within the ACC group but not the Placebo group, the CBPI, CSOM and VOS assessments were lower compared to day 0 and to day 14 (P<0.05). The relatively small number of dogs limited the statistical power of the pilot study to evaluate efficacy and safety of ACC. Study results support the conduct of larger, appropriately powered studies using similar assessments to confirm whether or not ACC may be a safe and effective treatment for OA in dogs.